Degradation of Humic Acid in Soil Aqueous Extract Using the Fenton Reaction and a Microbiological Technique - Nawaphorn Khumsiri; Ranjna Jindal; Nuttawan Yoswathana; Woranart Jonglertjunya (Agriculture and Natural Resources, 2010)
In this study, the degradation of humic acid (HA) extracted from soil in aqueous solution was carried out using the Fenton reaction and a microbiological technique. The Fenton reaction produced hydroxyl radicals (•OH) from the catalytic decomposition of hydrogen peroxide (H2O2) by the soluble ferrous ion (Fe2+) for use in the destruction of organic pollutants. At pH 3.0, the ratios of HA and H2O2 of 1:560 and the H2O2 and Fe2+ ratios of 5:1 showed the maximum percentage of HA removal. Thus, the optimal ratio of HA:H2O2:Fe2+ for HA removal appeared to be 1:560:112. However, the highest HA removal per gram of soil was 30% after 3 h when using a ratio of humic acid to reagents (H2O2 and Fe2+) of 1:11200:2240. The comparative evaluation of two microorganisms Pseudomonas fluorescens and Lactococcus lactis for the degradation of HA indicated the highest removal of about 28% when using Lactococcus lactis as a single culture for soil samples within 20 d.